2021
DOI: 10.3390/polym13162744
|View full text |Cite
|
Sign up to set email alerts
|

A New Conformal Cooling System for Plastic Collimators Based on the Use of Complex Geometries and Optimization of Temperature Profiles

Abstract: The paper presents a new design of conformal cooling channels, for application in collimator-type optical plastic parts. The conformal channels that are presented exceed the thermal and dynamic performance of traditional and standard conformal channels, since they implement new sections of complex topology, capable of meeting the high geometric and functional specifications of the optical part, as well as the technological requirements of the additive manufacturing of the mold cavities. In order to evaluate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 39 publications
(37 reference statements)
1
5
0
1
Order By: Relevance
“…However, achieving minimal cooling time and consistent temperature remains a significant challenge. During the cooling phase, optimizing the injection process is crucial for enhancing product quality or decreasing the injection cycle duration [13,14] . So, this research presented a novel methodology with multiobjective function-based heat transfer analysis of conformal cooling channels in the injection molding process.…”
Section: Introductionmentioning
confidence: 99%
“…However, achieving minimal cooling time and consistent temperature remains a significant challenge. During the cooling phase, optimizing the injection process is crucial for enhancing product quality or decreasing the injection cycle duration [13,14] . So, this research presented a novel methodology with multiobjective function-based heat transfer analysis of conformal cooling channels in the injection molding process.…”
Section: Introductionmentioning
confidence: 99%
“…In industrial practice, the warpage of molded parts is an even bigger problem than shrinkage. Warpage is a consequence of unequal shrinkage values [ 25 ]. The injection molding process significantly affects the warping phenomenon in the geometry obtained, due to non-uniformities in the mold wall [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [ 42 ] applied a model based on unit cells for the dimensioning of conformal cooling, the results obtained by Xu indicated a 15% reduction of the cycle time. Colmenero et al [ 43 ] performed a method to maximize the efficiency of shaped cooling channels manufactured by additive manufacturing. Research results showed that cooling and cycle time can be reduced by more than 50%.…”
Section: Introductionmentioning
confidence: 99%